2002
DOI: 10.1007/s198-002-8343-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Hip Fracture Risk Score for Assessing Elderly Women: The Melton Osteoporotic Fracture (MOF) Study

Abstract: Risk assessment for osteoporotic fracture within a primary care context, in old age, has received little attention. We aimed to develop such a risk score and assess its feasibility and validity. This was a 100% population-based, prospective cohort study, with a minimum 5 1/2 year follow-up among women aged 70 years and over, set in a large single general practice in Melton Mowbray, Leicestershire, UK. The main outcome measures were hip fracture, death and migration. Baseline measures included calcaneal broadba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 37 publications
2
49
1
2
Order By: Relevance
“…2,6,15,17 However, in a large epidemiological study of hip fracture contrasting risk factors between men and women, the associations with chronic medical disorders, physical activity, and cigarette smoking were generally similar for both genders. 18 This finding is consistent with the results of a previous British case-control study of hip fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,6,15,17 However, in a large epidemiological study of hip fracture contrasting risk factors between men and women, the associations with chronic medical disorders, physical activity, and cigarette smoking were generally similar for both genders. 18 This finding is consistent with the results of a previous British case-control study of hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Our results are comparable to other published reports. In the Melton Mowbray Osteoporotic Fracture Study, 17 it was found that a combination of readily obtained risk factors was capable of identifying elderly women who later sustained a hip fracture. These included weight, poor trunk maneuver, epilepsy, kyphosis, poor circulation of the foot, and short-term corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,10 Despite the use of only 4 clinical risk factors applied in a strict binary fashion in our FRAMO Index, its sensitivity and specifi city for 2-year hip fracture incidence were on par with those of previous studies with more complicated risk scoring. 5,8,11 Similar risk factors have been used in other studies, in which scores for predicting the risk of hip fracture within 3, 4, or 5 years were created. 4,5,11 In those studies, however, the variables of age or body weight were weighted, and a history of any type of fracture after age of 50 was used instead.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…4,9,10 Many individuals who have an elevated risk of hip fracture might be identifi ed by clinical risk factors alone. 4,5,11 Previously described risk factor models for hip fracture are fairly complicated, requiring several weighted variables. Six clinical risk factors (2 weighted) and BMD assessment predicted fractures in the Study of Osteoporotic Fractures (SOF), and this risk factor combination was validated in another elderly community-based female population, the European Patent Information and Document Service (EPIDOS) fracture study.…”
Section: Introductionmentioning
confidence: 99%